2021
DOI: 10.1177/1558944720988130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Functional and Symptomatic Outcomes After Vitamin D3 Administration in Carpal Tunnel Syndrome With Hypovitaminosis D

Abstract: Background Vitamin D deficiency is now recognized as an independent risk factor and is involved in the pathogenesis of carpal tunnel syndrome (CTS). The purpose of this study was to evaluate the effects of vitamin D3 supplementation on functional and symptomatic outcomes in CTS patients with vitamin D deficiency. Methods This was a prospective, single-arm study with a pretreatment or posttreatment quasi-experimental design. Carpal tunnel syndrome patients with vitamin D deficiency were treated with vitamin D3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Serum vitamin D levels increased significantly after vitamin supplement in the three studies which reported this [21, 35, 36], whereas one study did not detail the vitamin D level after supplementation [26]. The doses of oral vitamin D varied in each study, ranging from 7000 to 60,000 IU/week with a duration of 12 weeks in three studies [26, 35, 36] and 24 weeks in one study [21]. These clinical data and interventions in each included study are presented in Table 2.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Serum vitamin D levels increased significantly after vitamin supplement in the three studies which reported this [21, 35, 36], whereas one study did not detail the vitamin D level after supplementation [26]. The doses of oral vitamin D varied in each study, ranging from 7000 to 60,000 IU/week with a duration of 12 weeks in three studies [26, 35, 36] and 24 weeks in one study [21]. These clinical data and interventions in each included study are presented in Table 2.…”
Section: Resultsmentioning
confidence: 91%
“…The treatment outcomes were evaluated by visual analog scale (VAS) in 124 wrists of 97 patients, functional scores in 176 wrists of 176 patients, muscle strength in 84 wrists of 84 patients, and nerve conduction velocity in 216 wrists of 189 patients. CTS symptoms as evaluated by VAS scores were decreased significantly in two studies [35, 36]. Contrary to the pain scores, there were no statistically significant differences in motor power and median motor conduction velocity.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations